CypherDB: a novel architecture for outsourcing secure database processing - Chen,BHK; Cheung,PYS; Cheung,PYK; Kwok,Y-K (IEEE Transactions on Cloud Computing, 2018)
CypherDB addresses the problem of protecting the confidentiality of database stored externally in a cloud and enabling efficient computation over it to thwart any curious-but-honest cloud computing service provider. It works by encrypting the entire outsourced database and executing queries over the encrypted data using our novel CypherDB secure processor architecture. To optimize computational efficiency, our proposed processor architecture provides tightly-coupled datapaths that avoid information leakage during database access and query execution. Our simulation using a well-known database benchmark TPC-H over a commercial grade Database Management System (SQLite) demonstrates that our proposed architecture incurs an average of about 10 percent overhead when compared with the same set of operations without secure database processing.